Experimental study on flow and thermal characters of calcium chloride hydrate slurry - Suwono, Aryadi; Irsyad, M.; Indartono, Yuli S.; Pasek, Ari D.
Phase change material has been used as secondary refrigerant mixing ingredients to reduce energy consumption. Salt hydrate from calcium chloride with the composition of 55% calcium chloride dihydrate and 45% water matched with the temperature of chiller evaporator. Flow of slurry has given effect on the flow and heat transfer characteristics. Equipment used to know this is double pipe heat exchanger with flow counter flow. Pipe material is copper. The test results showed that the temperature salt hydrate containing solid particles. Salt hydrate slurry can improve the heat transfer coefficient, but the pressure drop and friction factor was also increased.
Keywords: Calcium chloride; Phase change material; Latent heat of fusion; Secondary refrigerant